An Overview of The Indonesian Government’s Plans In Anticipating And Overcoming The Food Crisis As A Result Of The G20 Summit - Purike, Era; Nur Azizah; Kunto Ajibroto; Priatna Kesumah; Nana Sujana (Cita konsultindo, 2023)
The G20 Summit ended in November 2022, and one key point discussed at the meeting was food crisis mitigation. Some issues must be pointed out to overcome and anticipate the food crisis, especially in Indonesia. Hence, this paper aims to overview the plan of the Indonesian government that should be taken to anticipate and overcome the food crisis in Indonesia as the implementation of the agreement of G20’s Summit. This research is conducted using the literature review research method, which provides the output of existing data as well as a description of a discovery that can be used as an example for future research studies in compiling or making a clear discussion of the contents of the problem to be studied. The main result of this study is that G20 members need to step up cooperation and coordination to work closely with international organizations, the private sector, civil society, and other partners for poverty alleviation and improvement of food security and nutrition, and work toward inclusive and sustainable development, leaving no one behind. Thus, they will promote: (i) resilient and sustainable agriculture and food systems, (ii) open, fair, predictable, transparent, and non-discriminatory agricultural trade to expand food availability and affordability for all, and (iii) innovative agri-preneurship through digital agriculture to improve farmers livelihood in rural areas.